Rainfall Extremes In Northern And Southern Central Java Coasts: Comparative Study Of ENSO And IOD Influences - Imawan Mashuri; Muzakkie, Muhammad Labieb; Duo Rahman Abdilah; Salsabila Nurul Izzah; Giarno (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2025)
The northern and southern coastal regions of Central Java frequently experience hydrometeorological disasters due to extreme rainfall. The relationship between extreme rainfall in these two areas is influenced by fluctuations in the Indian Ocean Dipole (IOD) and the El Niño-Southern Oscillation (ENSO). This study aims to compare the characteristics of extreme rainfall in the northern and southern coastal regions of Central Java in relation to ENSO and IOD phases. The analysis applies extreme rainfall indices (RX1D, RX5D, CDD, CWD) and Spearman-rank correlation to understand the influence of these climate phenomena and indices. The results show that RX1D and RX5D values are higher during La Niña and negative IOD phases, especially in the rainy season, while El Niño and positive IOD phases reduce their intensity. CWD is longer during La Niña, but positive IOD decreases the number of rainy days, particularly during the dry season. In contrast, CDD increases significantly during El Niño and positive IOD, which intensify dry conditions, especially along the southern coast. Spearman-rank correlations indicate a negative relationship between ENSO/IOD and RX1D, RX5D, and CWD, and a positive relationship with CDD, with stronger impacts during the dry season and second transitional period (SON), as well as varying characteristics between the two coasts. These findings underscore the necessity for adaptation and mitigation strategies in response to extreme rainfall characteristics, particularly when ENSO and IOD phases coincide, with stronger impacts observed along the southern coast.